2019
DOI: 10.1051/swsc/2019015
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive disturbances of the geomagnetic field as a cause of induced currents of electric power lines

Abstract: Geomagnetically induced currents (GICs) represent a significant challenge for society on a stable electricity supply. Space weather activates global electromagnetic and plasma processes in the near-Earth environment, however, the highest risk of GICs is related not directly to those processes with enormous energy yield, but too much weaker, but fast, processes. Here we consider several typical examples of such fast processes and their impact on power transmission lines in the Kola Peninsula and in Karelia: inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(78 citation statements)
references
References 56 publications
6
71
0
1
Order By: Relevance
“…The westward current enhancements are recorded as southward deflections of the magnetic field, as observed by ground-based magnetometers. To a good approximation, the direction of any fluctuation, dB H , measured at the ground is 90°anticlockwise from the ionospheric current direction (as viewed from above the current sheet) assuming planar electromagnetic wave propagation and minimal horizontal gradients in ground conductivity Belakhovsky et al, 2019).…”
Section: Gics and Magneto-ionospheric Currentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The westward current enhancements are recorded as southward deflections of the magnetic field, as observed by ground-based magnetometers. To a good approximation, the direction of any fluctuation, dB H , measured at the ground is 90°anticlockwise from the ionospheric current direction (as viewed from above the current sheet) assuming planar electromagnetic wave propagation and minimal horizontal gradients in ground conductivity Belakhovsky et al, 2019).…”
Section: Gics and Magneto-ionospheric Currentsmentioning
confidence: 99%
“…Sudden commencements (SC) (a general term for both SSC and SI) occur in response to step changes in solar wind dynamic pressure that cause a sudden increase in the Chapman-Ferraro current flowing eastward along the dayside magnetopause boundary (Chapman & Ferraro, 1931;Milan et al, 2017). They typically have a magnitude of several tens of nT/min at low latitudes, but may occasionally exceed 120 nT/min (Fiori et al, 2014;Carter et al, 2015) and have been associated with GIC disturbances in HV electricity networks (Kappenman, 2003(Kappenman, , 2004Marshall et al, 2012;Fiori et al, 2014;Zhang et al, 2015;Belakhovsky et al, 2017Belakhovsky et al, , 2019.…”
Section: Gics and Magneto-ionospheric Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, substorm-injected energetic particles can lead to surface charging in satellites, which can damage surface materials and underlying components (Gubby & Evans, 2002;Horne et al, 2013;O'Brien, 2009). Substorms can also produce geomagnetically induced currents that adversely impact electric supply networks (Belakhovsky et al, 2019;Freeman et al, 2019). Forecasting substorm activity has therefore been a topic of practical as well as theoretical space weather interest.…”
Section: 1029/2019sw002251mentioning
confidence: 99%
“…A study done by Pirjola (2002) describes the occurrence of erroneous traffic signals on railways caused by geomagnetically induced currents. Other studies have reported the effects of GIC's on electric power grids (Belakhovsky et al 2019), trans-oceanic cables (Lanzerotti et al 1995) and pipelines (Pulkkinen et al 2001).…”
Section: Introductionmentioning
confidence: 99%